2017
DOI: 10.5056/jnm16020
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Complaints Are Significantly Associated with Chronic Uninvestigated Dyspepsia and Its Symptoms: A Large Cross-sectional Population Based Study

Abstract: Background/AimsSomatization may influence persistence and severity of symptoms in gastrointestinal diseases. Some studies suggest that somatization is associated with chronic uninvestigated dyspepsia (CUD); however, the association is unclear. We aimed to determine the association between the profiles of somatic complaints with CUD and its symptoms. MethodsIn a cross-sectional study conducted on 4763 Iranian adults, somatic complaints were assessed using a comprehensive 31-items questionnaire. Patients with CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…The occurrence of PDS symptoms was in line with the frequency reported in previous studies ( 15 , 20 ). Furthermore, it has also been reported that patients with chronic uninvestigated dyspepsia have increased occurrence of joint and back pain ( 27 ), and therefore, it is conceivable that some of these patients might also have comorbid JHS.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of PDS symptoms was in line with the frequency reported in previous studies ( 15 , 20 ). Furthermore, it has also been reported that patients with chronic uninvestigated dyspepsia have increased occurrence of joint and back pain ( 27 ), and therefore, it is conceivable that some of these patients might also have comorbid JHS.…”
Section: Discussionmentioning
confidence: 99%
“…The factor scores for each profile were computed by summing up items of psychosomatic symptoms weighted by their factor loadings and assigned to each participant. More details about the results of factor analysis on psychosomatic symptoms are presented elsewhere [14,23]. In this study, quantitative and qualitative variables were expressed as mean (SD) and frequency (percentage), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a separate mini survey on 100 randomly selected participants in order to assess the reliability of this questionnaire. There was a strong internal reliability based on Cronbach's alpha score of 0.903 [23].…”
Section: Assessment Of Psychosomatic/somatoform Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we settled a validated questionnaire based on 31 items in SEPAHAN's questionnaires common with the 47-items questionnaire used in the Lacourt et al's study (29), and "the patient health questionnaire (PHQ)" (30) as valid and standard tools for the assessment of somatoform symptoms. The reliability of this instrument has been evaluated previously (31) and showed a strong internal reliability with a Cronbach's alpha score of 0.903. The 31-items questionnaire was used to examine the frequency of somatoform symptoms.…”
Section: Assessment Of Somatoform Symptomsmentioning
confidence: 99%